2015
DOI: 10.4103/2394-5079.168725
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma and type 2 diabetes mellitus: two cases highlighting changes in tumor glycogen content

Abstract: This article reports two patients with hepatocellular carcinoma (HCC) and type 2 diabetes mellitus (T2DM), who showed marked changes in hepatocellular glycogen content. Periodic acid-Schiff (PAS)-positive and diastase-PAS-negative (glycogen-storing) hepatocytes were detected in both background liver parenchyma and in HCC tissues. In HCC tissues, the number of glycogen-storing cells resembling hepatocytes was considerably reduced and unevenly distributed as compared with hepatocytes in background liver. To be k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[1] It was suggested that the latter was associated with appearance of a Warburg type glycolysis [1] and discussed in some detail. [2] Cytokeratins (CKs), the intermediate filament (IF) proteins of epithelia, are sub-divided into type I (CK9-20) and type II (CK1-8) and expressed as type I/II pairs in a cell differentiation manner.…”
Section: Sirmentioning
confidence: 99%
“…[1] It was suggested that the latter was associated with appearance of a Warburg type glycolysis [1] and discussed in some detail. [2] Cytokeratins (CKs), the intermediate filament (IF) proteins of epithelia, are sub-divided into type I (CK9-20) and type II (CK1-8) and expressed as type I/II pairs in a cell differentiation manner.…”
Section: Sirmentioning
confidence: 99%